2018
DOI: 10.7567/jjap.57.091302
|View full text |Cite
|
Sign up to set email alerts
|

Gettering mechanism in hydrocarbon-molecular-ion-implanted epitaxial silicon wafers revealed by three-dimensional atom imaging

Abstract: The interaction of iron (Fe) with defects induced by a high hydrocarbon-molecular-ion-implantation dose of 1 × 1016 cm−2 in a Czochralski-grown silicon substrate and an epitaxial growth layer was investigated using secondary ion mass spectroscopy, transmission electron microscopy, and laser-assisted atom probe tomography (L-APT). High-dose hydrocarbon-molecular-ion-implantation formed two types of defects in the projection range: stacking faults and carbon agglomerates. It was demonstrated that the dominant ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Our proposal gettering design concept for silicon wafer production leaves intact gettering sinks in the epitaxial layer after backside grinding and the CMP process in BSI fabrication. We previously reported that the metallic impurity gettering capability of this wafer was higher than that in the CZ silicon substrate using APT [60,61]. Because the gettering capability depends on the depth profile of gettering sinks in the silicon epitaxial layer.…”
Section: Gettering Technology Design For Back-side-illuminated Cmomentioning
confidence: 96%
See 1 more Smart Citation
“…Our proposal gettering design concept for silicon wafer production leaves intact gettering sinks in the epitaxial layer after backside grinding and the CMP process in BSI fabrication. We previously reported that the metallic impurity gettering capability of this wafer was higher than that in the CZ silicon substrate using APT [60,61]. Because the gettering capability depends on the depth profile of gettering sinks in the silicon epitaxial layer.…”
Section: Gettering Technology Design For Back-side-illuminated Cmomentioning
confidence: 96%
“…CMOS image sensor manufacturers require for a way of dealing with these issues. We propose using hydrocarbon–molecular–ion–implanted epitaxial silicon wafer [60,61].…”
Section: Gettering Technology Design For Back-side-illuminated Cmomentioning
confidence: 99%
“…In a previous study, we demonstrated that these 5 nm defects induced by a high C 3 H 6 -ion implantation dose of 1 × 10 16 cm −2 in the CZ-Si substrate and the first epitaxial layer also consisted of C and I agglomerates [ 38 ]. L-APT data in high-dose C 3 H 6 -ion-implanted samples indicated a difference in the O distribution between the 5 nm defects induced in the CZ-Si substrate and the first epitaxial layer [ 38 , 39 ]. This implies a significant difference in the morphology of 5 nm defects between the CZ-Si substrate and the first epitaxial layer.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous study, we found that defects formed upon C 3 H 6 -ion-implantation at a high dose of 1 × 10 16 cm −2 in the first epitaxial layer are C– I agglomerates without O atoms [ 38 , 39 ]. This tendency of the O distribution in defects in the previous study is in good agreement with that of defects in the double epitaxial Si wafer formed after the device process in the current study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation